ANALISIS BRAND POSITIONING SEPEDA MOTOR HONDA DAN YAMAHA PADA PENGGUNA SEPEDA MOTOR DI PROVINSI BANTEN - Sutisna, Sutisna (Yayasan Education and Social Center, 2024)
This research analyzes the brand positioning of Honda and Yamaha motorbikes in Banten Province. Brand positioning is a key element in marketing that depicts a unique value proposition to consumers. This study uses a comparative descriptive method with data collected through questionnaires to 151 respondents. The sampling technique used was convenience sampling. The research results show that Honda's brand positioning, with the tagline